Immunotherapy and Targeting the Tumor Microenvironment: Current Place and New Insights in Primary Pulmonary NUT Carcinoma - Li, Xiang; Shi, Hui; Zhang, Wei; Bai, Chong; He, Miaoxia; Ta, Na; Huang, Haidong; Ning, Yunye; Fang, Chen; Qin, Hao; Dong, Yuchao (Frontiers in Oncology, 2021)
Primary pulmonary nuclear protein of testis carcinoma is a rare and highly aggressive malignant tumor. It accounts for approximately 0.22% of primary thoracic tumors and is little known, so it is often misdiagnosed as pulmonary squamous cell carcinoma. No effective treatment has been formed yet, and the prognosis is extremely poor. This review aims to summarize the etiology, pathogenesis, diagnosis, treatment, and prognosis of primary pulmonary nuclear protein of testis carcinoma in order to better recognize it and discuss the current and innovative strategies to overcome it. With the increasing importance of cancer immunotherapy and tumor microenvironment, the review also discusses whether immunotherapy and targeting the tumor microenvironment can improve the prognosis of primary pulmonary nuclear protein of testis carcinoma and possible treatment strategies. We reviewed and summarized the clinicopathological features of all patients with primary pulmonary nuclear protein of testis carcinoma who received immunotherapy, including initial misdiagnosis, disease stage, immunohistochemical markers related to tumor neovascularization, and biomarkers related to immunotherapy, such as PD-L1 (programmed death-ligand 1, PD-L1) and TMB (tumor mutational burden, TMB). In the meanwhile, we summarized and analyzed the progression-free survival (PFS) and the overall survival (OS) of patients with primary pulmonary nuclear protein of testis carcinoma treated with PD-1 (programmed cell death protein 1, PD1)/PD-L1 inhibitors and explored potential population that may benefit from immunotherapy. To the best of our knowledge, this is the first review on the exploration of the tumor microenvironment and immunotherapy effectiveness in primary pulmonary nuclear protein of testis carcinoma.